Evaluation of teamwork in the Maternal Intensive Care Unit in relation to the Culture of Patient Safety (Research, Society and Development, 2022)
The objective of this study was to evaluate the teamwork in a Maternal Intensive Care Unit (MICU), from the perspective of the multiprofessional health team. This is a cross-sectional study, conducted between February and March 2021, which used for data collection the Hospital Survey on Patient Safety Culture questionnaire, which assesses 12 dimensions of Patient Safety Culture (CSP). For the purposes of this study, the items that make up the dimensions "Teamwork within the unit" and "Teamwork between units" were assessed, thus constituting 8 items. Forty professionals participated in the study. When analyzing the items evaluated, it was observed that 3 were considered areas of strength for the CSP, 1 as a neutral area and 4 classifieds as weak. It can be stated that from the perspective of the multiprofessional team of the UTIM, teamwork within the unit is strong for the CSP, because they treat each other with respect, supporting each other, besides working as a team when there is a lot of work to be done. Regarding teamwork between the units, the professionals believe that the sectors of the maternity hospitals are not well coordinated among themselves and that there is not good cooperation between the units that need to work together.